Space filling of β-cyclodextrin and β-cyclodextrin derivatives by volatile hydrophobic guests - Fourmentin, Sophie; Ciobanu, Anca; Landy, David; Wenz, Gerhard (Beilstein Journal of Organic Chemistry, 2013)
The inclusion of volatile derivatives of benzene and cyclohexane in β-cyclodextrin (β-CD), hydroxypropyl-β-CD, and hydrophilic β-CD-thioethers was investigated by static headspace gas chromatography (HS-GC) and molecular modelling. The obtained binding constants strongly increase with the amount of space filling of the CD cavity and the salt concentration. β-CD thioethers show a 3–10 times higher binding potential than native β-CD.
Keywords: cyclodextrins; inclusion compound; molecular modelling; space filling; static headspace gas chromatography; vapor pressure

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

(untitled) - Sanemasa, I.; Akamine, Y. (Bull. Chem. Soc. Jpn., 1987)

(untitled) - Höfler, T.; Wenz, G. (J. Inclusion Phenom. Mol. Recognit. Chem., 1996)

(untitled) - Szaniszló, N.; Fenyvesi, É.; Balla, J. (J. Inclusion Phenom. Macrocyclic Chem., 2005)

(untitled) - Gelb, R. I.; Schwartz, L. M. (J. Inclusion Phenom. Mol. Recognit. Chem., 1989)

(untitled) - Briggner, L.-E.; Ni, X.-R.; Tempesti, F.; Wadsö, I. (Thermochim. Acta, 1986)

(untitled) - Eftink, M. R.; Andy, M. L.; Bystrom, K.; Perlmutter, H. D.; Kristol, D. S. (J. Am. Chem. Soc., 1989)

(untitled) - Hinze, W. L. (Sep. Purif. Methods, 1981)

(untitled) - Liu, L.; Guo, Q.-X. (J. Inclusion Phenom. Macrocyclic Chem., 2002)

(untitled) - Tanford, C. (J. Am. Chem. Soc., 1962)

(untitled) - Israelachvili, J.; Wennerström, H. (Nature, 1996)

(untitled) - Schneider, H.-J.; Yatsimirsky, A. K. (Chem. Soc. Rev., 2008)

(untitled) - Schneider, H.-J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Snyder, P. W.; Mecinović, J.; Moustakas, D. T.; Thomas, S. W., III; Harder, M.; Mack, E. T.; Lockett, M. R.; Héroux, A.; Sherman, W.; Whitesides, G. M. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Biedermann, F.; Uzunova, V. D.; Scherman, O. A.; Nau, W. M.; De Simone, A. (J. Am. Chem. Soc., 2012)

(untitled) - Eldridge, M. D.; Murray, C. W.; Auton, T. R.; Paolini, G. V.; Mee, R. P. (J. Comput.-Aided Mol. Des., 1997)

(untitled) - Moitessier, N.; Englebienne, P.; Lee, D.; Lawandi, J.; Corbeil, C. R. (Br. J. Pharmacol., 2008)

(untitled) - Wenz, G. (Clin. Drug Invest., 2000)

(untitled) - Decock, G.; Landy, D.; Surpateanu, G.; Fourmentin, S. (J. Inclusion Phenom. Macrocyclic Chem., 2008)

(untitled) - Shao, D.; Sheng, G.; Chen, C.; Wang, X.; Nagatsu, M. (Chemosphere, 2010)

(untitled) - Mahlambi, M. M.; Malefetse, T. J.; Mamba, B. B.; Krause, R. W. (J. Polym. Res., 2010)

(untitled) - Rölling, P.; Lamers, M.; Staudt, C. (J. Membr. Sci., 2010)

(untitled) - Baruch-Teblum, E.; Mastai, Y.; Landfester, K. (Eur. Polym. J., 2010)

(untitled) - Cassez, A.; Kania, N.; Hapiot, F.; Fourmentin, S.; Monflier, E.; Ponchel, A. (Catal. Commun., 2008)

(untitled) - Schwartz, A.; Bar, R. (Appl. Environ. Microbiol., 1995)

(untitled) - Mavridis, I. M.; Hadjoudis, E. (Carbohydr. Res., 1992)

(untitled) - Enright, G. D.; Udachin, K. A.; Ripmeester, J. A. (CrystEngComm, 2010)

(untitled) - Sanemasa, I.; Wu, J.-S.; Toda, K. (Bull. Chem. Soc. Jpn., 1997)

(untitled) - Müller, B. W.; Brauns, U. (J. Pharm. Sci., 1986)

(untitled) - Brewster, M. E.; Loftsson, T. (Pharmazie, 2002)

(untitled) - Armstrong, D. W.; Li, W.; Chang, C. D.; Pitha, J. (Anal. Chem., 1990)

(untitled) - Thiele, C.; Auerbach, D.; Jung, G.; Wenz, G. (J. Inclusion Phenom. Macrocyclic Chem., 2011)

(untitled) - Steffen, A.; Thiele, C.; Tietze, S.; Strassnig, C.; Kämper, A.; Lengauer, T.; Wenz, G.; Apostolakis, J. (Chem.–Eur. J., 2007)

(untitled) - Fourmentin, S.; Outirite, M.; Blach, P.; Landy, D.; Ponchel, A.; Monflier, E.; Surpateanu, G. (J. Hazard. Mater., 2007)

(untitled) - Blach, P.; Fourmentin, S.; Landy, D.; Cazier, F.; Surpateanu, G. (Chemosphere, 2008)

(untitled) - Lantz, A. W.; Wetterer, S. M.; Armstrong, D. W. (Anal. Bioanal. Chem., 2005)

(untitled) - Ciobanu, A.; Mallard, I.; Landy, D.; Brabie, G.; Nistor, D.; Fourmentin, S. (Carbohydr. Polym., 2012)

(untitled) - Wenz, G. (Beilstein J. Org. Chem., 2012)

(untitled) - Wang, H. M.; Wenz, G. (Chem.–Asian J., 2011)

(untitled) - Breslow, R. (Acc. Chem. Res., 1991)

Cyclodextrins - Szejtli, J. (Chemistry, Physical and Biological Properties of Cyclodextrins, 1996)

(untitled) - Fini, P.; Castagnolo, M.; Catucci, L.; Cosma, P.; Agostiano, A. (J. Therm. Anal. Calorim., 2003)

(untitled) - Wenz, G.; Strassnig, C.; Thiele, C.; Engelke, A.; Morgenstern, B.; Hegetschweiler, K. (Chem.–Eur. J., 2008)

(untitled) - Dron, P. I.; Fourmentin, S.; Cazier, F.; Landy, D.; Surpateanu, G. (Supramol. Chem., 2008)

(untitled) - Mohamadi, F.; Richards, N. G. J.; Guida, W. C.; Liskamp, R.; Lipton, M.; Caufield, C.; Chang, G.; Hendrickson, T.; Still, W. C. (J. Comput. Chem., 1990)

(untitled) - Cheng, A.; Best, S. A.; Merz, K. M., Jr; Reynolds, C. H. (J. Mol. Graphics Mod., 2000)